Higher Order Aberration and Astigmatism in Children with Hyperopic Amblyopia - Choi, Seung Kwon (Korean J Ophthalmol, 2016)
PURPOSE: To investigate the changes in corneal higher-order aberration (HOA) during amblyopia treatment and the correlation between HOA and astigmatism in hyperopic amblyopia children. METHODS: In this retrospective study, a total of 72 eyes from 72 patients ranging in age from 38 to 161 months were included. Patients were divided into two groups based on the degree of astigmatism. Corneal HOA was measured using a KR-1W aberrometer at the initial visit and at 3-, 6-, and 12-month follow-ups. Correlation analysis was performed to assess the association between HOA and astigmatism. RESULTS: A total of 72 patients were enrolled in this study, 37 of which were classified as belonging to the higher astigmatism group, while 35 were assigned to the lower astigmatism group. There was a statistically significant difference in success rate between the higher and lower astigmatism groups. In both groups, all corneal HOAs were significantly reduced during amblyopia treatment. When comparing the two groups, a significant difference in coma HOA at the 12-month follow-up was detected (p = 0.043). In the Pearson correlation test, coma HOA at the 12-month follow-up demonstrated a statistically significant correlation with astigmatism and a stronger correlation with astigmatism in the higher astigmatism group than in the lower astigmatism group (coefficient values, 0.383 and 0.284 as well as p = 0.021 and p = 0.038, respectively). CONCLUSIONS: HOA, particularly coma HOA, correlated with astigmatism and could exert effects in cases involving hyperopic amblyopia.